2015
DOI: 10.5114/reum.2015.50555
|View full text |Cite
|
Sign up to set email alerts
|

Total ankle replacement – surgical treatment and rehabilitation

Abstract: Functions of the ankle joint are closely connected with the gait and ability to maintain an upright position. Degenerative lesions of the joint directly contribute to postural disorders and greatly restrict propulsion of the foot, thus leading to abnormal gait.Development of total ankle replacement is connected with the use of the method as an efficient treatment of joint injuries and continuation of achievements in hip and knee surgery. The total ankle replacement technique was introduced as an alternative to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…We believe that partial weight-bearing and maintaining immobilization for 6 weeks is a reasonable approach facilitating bone ongrowth. It is advisable to remember the remark by Prusinowska et al [ 24 ] that supination and pronation exercises should be started only when complete active motions of flexion and extension are restored, as failure to follow that principle may lead to the destabilization of the ankle joint and damage of the prosthesis fixing. It is particularly important to intensify PT after removing the walker boot and to implement balance and proprioception training during this rehabilitation phase.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that partial weight-bearing and maintaining immobilization for 6 weeks is a reasonable approach facilitating bone ongrowth. It is advisable to remember the remark by Prusinowska et al [ 24 ] that supination and pronation exercises should be started only when complete active motions of flexion and extension are restored, as failure to follow that principle may lead to the destabilization of the ankle joint and damage of the prosthesis fixing. It is particularly important to intensify PT after removing the walker boot and to implement balance and proprioception training during this rehabilitation phase.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of this deformity increases with age. Prusinowska et al [9] found that the incidence is 3% in individuals aged 15-30, 9% in those aged 31-60, and 16% in individuals above 60 years of age.…”
Section: Bunionsmentioning
confidence: 99%
“…It is often caused by biological and mechanical occurrences disordering a synthesis and triggering the defeneration of the articular cartilage, in chondrocytes and an extracellular matrix as well as in the subchondral layer of the bone [5,6,7,8]. There are several conditions causing limitations in the mobility of the shoulder joint, including [7,9]:…”
Section: Replacement Of the Shoulder Jointmentioning
confidence: 99%